A Robust Controller Design for a Multimachine Power System - Bandekas, D.; Tsirigotis, G.; Antoniadis, P.; Vordos, N. (Elektronika ir Elektrotechnika, 2006)
An excitation control method using state feedback is applied to a synchronous generator in a multimachine power system, while a phase to earth unsymmetrical fault or a three-phase symmetrical fault being applied. The simulation results of the study show that the excitation controller performs satisfactorily in a multimachine environment, when operating in conjunction with the conventional regulators of the other system generators. The proposed method for designing implementable robust excitation controllers is relatively simple to apply. Ill. 5, bibl. 13 (in English; summaries in Lithuanian, English and Russian).